Evaluating the role of protective creams on the cutaneous penetration of Ni nanoparticles. (1st July 2023) - Magnano, Greta Camilla; Carton, Flavia; Boccafoschi, Francesca; Marussi, Giovanna; Cocetta, Elisa; Crosera, Matteo; Adami, Gianpiero; Voinovich, Dario; Larese Filon, Francesca
Abstract: There is an increase of application of Nickel in the form of nanoparticles (NiNPs) in several fields including modern metallurgy, bioengineering, and medicine. Such growth of the areas of application is actually accompanied with an increase of exposure to Nickel, thus an intensification of the negative effects, the most frequent being the allergic contact dermatitis. Indeed, due to their smaller size, and therefore their higher surface area, NiNPs can release more Ni ions compared to bulk material, that can penetrate and permeate through the skin. To reduce the Ni cutaneous penetration, barrier creams (BC) are applied on the skin surface. There is little information, however, on the efficiency of such commercial protective creams on decreasing Ni cutaneous penetration. For this reason, the objective of the current study was to investigate the protective role of one commercially available formulation for Ni (Nik-L-Block™ containing a chelating agent) and one moisturizing cream (Ceramol 311 basic cream without chelating agent), following exposure to NiNPs, using in vitro Franz cells, as well as the cytotoxicity of NiNPs in primary human dermal fibroblasts was studied. Our results demonstrated that although both tested formulations can decrease Ni accumulation in the skin (4.13 ± 1.74 μg/cm 2 for Nik-L-Block™ and 7.14 ± 1.46 μg/cm 2 for Ceramol 311 basic cream); there are significant differences between the two creams (p = 0.004). Based on the experimental evidence, we therefore conclude that the composition of such formulations has an imperative role for dermal uptake of Ni. Finally, NiNPs showed no cytotoxic effect on cultured human dermal fibroblasts after 24 and 72 h. Graphical abstract: Image 1 Highlights: NiNPs can release more Ni ions compared to bulk material due to the small size/high surface. NiNPs can permeate and penetrate through the skin layers. Commercially available creams (Nik-L-Block® and Ceramol 311) reduce skin absorption of Ni. No cytotoxic effect was observed for NiNPs and NiCl2 on cultured human dermal fibroblasts.